Mobile suit Gundam, the origin MSD. Cucuruz Doan's Island, 1 / story & art Junji Ohno ; [translation C.T. Cockrell]. - Ohno, Junji; Yasuhiko, Yoshikazu, 1947- (Kodansha, 2024)
"Based on the legendary "lost" episode from the First Gundam TV series, this is the story of Cucuruz Doan like you’ve never seen it before. Created as a spinoff of original character designer and animation director Yoshikawa Yasuhiko’s own manga retelling of First Gundam in Mobile Suit Gundam: THE ORIGIN, this 5-volume series explores the ramifications of Cucuruz Doan’s actions from the perspective of the Zeon soldiers under his command. Gundam veteran Junji Ohno brings us brand-new characters and a new view of the development of the original mobile suits, all with the imprimatur of Yasuhiko himself."--Back cover.